Effect of stocking density on Growth and Survival rate Mangrove Shells, Polymesoda expansa, seeds in Dumai Coastal Waters of Riau Province. - Asri, Zainul; Nasution, Syafruddin; ', Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in November-December 2016 in the coastal waters of Dumai, Riau Province. This research aims to determine the growth and survival rate of seeds of mangrove shells P. expansa in natural habitats with different densities. This research uses experimental method. This research consists of one treatment that is with stocking density of three levels of 20, 25 and 30 individuals / container. The container used is a pond made of net (2 mesh size) with a size of 50x50 cm. The results showed that the best growth was found in the treatment with the density of 20 individuals / containers. Also, the best survival rate was found in the treatment of 20 individuals / containers of 98.6% size.Keywords : Polymesoda expansa,seeds Growth and Graduation rate, Stocking Density, Dumai.